The Utilization of Wattpad in Enhancing Students' Creative Writing Skills: A Social Constructivist Approach - Salsah Br Nainggolan; Joice Stefanie Ginting; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Creative writing plays an important role in developing students’ imagination, self- expression, and language competence in the digital era. However, many learners still struggle with generating ideas, maintaining motivation, and gaining confidence in writing. This study aims to analyze how the use of Wattpad, viewed through the Social Constructivist framework, can enhance students’ creative writing skills, motivation, and confidence. This research applies a qualitative descriptive approach supported by survey data from 30 high school students who actively use Wattpad. The results show that 95.7% of respondents have used Wattpad before, with most of them using it to read and learn from other writers. A total of 60.9% of respondents stated that reading other writers’ works was the most helpful for improving their writing, while 17.4% highlighted peer comments and feedback as additional support. Despite its benefits, 43.5% of students mentioned difficulty in organizing ideas as their main challenge. Open-ended responses revealed that positive feedback and community interaction on Wattpad helped increase students’ motivation and confidence in writing. The discussion emphasizes that the social interaction and feedback features of Wattpad foster collaborative learning, aligning with Vygotsky’s concepts of scaffolding and the Zone of Proximal Development. These findings suggest that integrating Wattpad into writing instruction can effectively enhance students’ creativity, critical thinking, and confidence in producing literary works.